Kickstart 2025 with Creative Classroom Innovations - Wan Noor Farah, Wan Shamsuddin; Umi Kalsom, Masrom; Nik Aloesnita, Nik Mohd Alwi; Nor Saradatul Akmar, Zulkifli; Danakorn Nincarean, Eh Phon; Muhammad Nur Adilin, Mohd Anuardi (UMPSA, 2025)
2025 brings new opportunities for educators to explore more unique ways to appeal to our students by bringing in new innovations and technology in the class. In line with Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) tagline, “Technology for Society”, this initiative is sure to resonate with our students, who are often regarded as digital natives. Here are some cutting-edge innovations for you to try in your classroom this year.